Application of Lime and Gypsum and Their Effect on Micronutrients (Fe, Zn, Mn, and Cu) Uptake of Sugarcane Planted in Central Lampung Ultisols - Christoporus Sudradjat Widiarso; Benito Heru Purwanto; Eko Hanudin; Azwar Ma’as (Jurnal Ilmu Pertanian, 2017)
Most of sugarcane are cultivated on Ultisols with low inherent soil fertility in Central Lampung. This experiment aimed to observe the effect of lime (CaCO3) and gypsum (Ca2SO4) on Fe, Zn, Mn, and Cu uptake of sugarcane. The experiment was conducted in Experimental Research Field of Gula Putih Mataram Enterprise, Central Lampung District. The experiment was designed using a split-plot, which consisted of lime application as the main plot and gypsum application as the sub plotwith three replications. The results showed that there were no significant influence of lime and gypsum application on micronutrient content of the soil. However, application of 2 and 3 tons of lime/ha could reduce soil Fe content about 349.86 and 328.07 ppm respectively within 0-20 cm soil in depthand it was significantly lower than comparing to Fe content (around 457.68 ppm) in control. Similarly, the effect of gypsum application at 0.25 ton.ha-1 decreased Fe content (355.42 ppm), while Fe content of non-gypsum application soil showed around 410.34 ppm. The analysis of other micronutrients did not indicate asignificant effect of lime or gypsum application.